Operando Magnetometry Probing the Charge Storage Mechanism of CoO Lithium‐Ion Batteries. Issue 12 (12th February 2021) - Li, Hongsen; Hu, Zhengqiang; Xia, Qingtao; Zhang, Hao; Li, Zhaohui; Wang, Huaizhi; Li, Xiangkun; Zuo, Fengkai; Zhang, Fengling; Wang, Xiaoxiong; Ye, Wanneng; Li, Qinghao; et al.
Abstract: Cobalt oxide (CoO) is a promising electrode for high‐energy‐density Li‐ion batteries (LIBs), where the charge storage is believed to take place solely during the electrochemical oxidation/reduction processes. However, this simple picture has been increasingly challenged by reported anomalously large storage capacities, indicating the existence of undiscovered extra charge reservoirs inside the system. Here, an advanced operando magnetometry technology is employed to monitor the magnetization variation of the CoO LIBs in real time and, in this particular system, it is clearly demonstrated that the anomalous capacity is associated with both the reversible formation of a spin capacitor and the growth of a polymeric film at low voltages. Furthermore, operando magnetometry provides direct evidence of the catalytic role of metallic Co in assisting the polymeric film formation. These critical findings help pave the way for better understanding of the charge storage mechanisms of transition‐metal oxides and further utilizing them to design novel electrode materials. Abstract : The charge storage mechanisms in CoO lithium‐ion batteries are demonstrated, based on the interpretation of the results of operando magnetometry. They involve the well‐known conversion reactions, the formation of a spin capacitor, and the growth of polymeric films. More importantly, direct evidence strongly supporting the catalytic role of metallic Co in assisting the polymeric film formation is obtained.